Urolithiasis Is a Risk Factor for Uroseptic Shock and Acute Kidney Injury in Patients With Urinary Tract Infection - Hsiao, Chih-Yen; Chen, Tsung-Hsien; Lee, Yi-Chien; Hsiao, Meng-Chang; Hung, Peir-Haur; Chen, Yih-Yuan; Wang, Ming-Cheng (Frontiers in Medicine, 2019)
Urinary tract infection (UTI) is a common complication in patients with urolithiasis. This study aimed to compare clinical manifestations and treatment outcomes among UTI patients with or without urolithiasis. It also focused on identifying relationships among urolithiasis, uroseptic shock, and acute kidney injury (AKI). This retrospective study enrolled hospitalized UTI patients who underwent imaging in an acute care setting from January 2006 to March 2015. Of 662 participants enrolled, 113 (17.1%) had urolithiasis, 107 (16.2%) developed uroseptic shock, and 184 (27.8%) developed AKI. A multivariate logistic regression analysis showed that in UTI patients, urolithiasis is associated with an increased risk of uroseptic shock (OR 1.80, 95% CI: 1.08–3.02, P = 0.025), AKI (OR 1.95, 95% CI: 1.22–3.12, P = 0.005), and bacteremia (OR 1.68, 95% CI: 1.08–2.64, P = 0.022). Urolithiasis is common in UTI patients and is associated with an increased risk of uroseptic shock and AKI.